2022
DOI: 10.1002/ajh.26536
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with light chain amyloidosis treated with bortezomib, cyclophosphamide, and dexamethasone ± daratumumab: Results from the ANDROMEDA study

Abstract: In the phase 3 ANDROMEDA trial, patients treated with daratumumab, bortezomib, cyclophosphamide, and dexamethasone (D‐VCd) had significantly higher rates of organ and hematologic response compared with patients who received VCd alone. Here, we present patient‐reported outcomes (PROs) from the ANDROMEDA trial. PROs were assessed through cycle 6 using three standardized questionnaires. Treatment effect through cycle 6 was measured by a repeated‐measures, mixed‐effects model. The magnitude of changes in PROs vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…The QoL of transplant‐ineligible patients, achieving very good partial response//CR, improves steadily up to 2 years after treatment but remains lower than that of the population norm. Improvement of QoL is, also, associated with a survival benefit 9,10 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The QoL of transplant‐ineligible patients, achieving very good partial response//CR, improves steadily up to 2 years after treatment but remains lower than that of the population norm. Improvement of QoL is, also, associated with a survival benefit 9,10 …”
Section: Resultsmentioning
confidence: 99%
“…The arsenal of therapeutic options for AL amyloidosis has increased in recent years and QoL improvement has become recognised by regulatory authorities as important and required for drug approval. Nevertheless, there is no consistency in the QLQs used between the various trials, with some referring to more than one 10–14 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, on the FACT/GOG-Ntx, small but significant improvements in neurotoxicity and sensory summary scores, as well as seven individual items, were observed in favor of ixazomib-dexamethasone relative to PC. It is possible that these measures may not be sufficiently sensitive to detect symptom burden or true decrements in underlying disease in patients with relapsed/ refractory AL amyloidosis.A prior analysis of PROs from the phase 3 ANDROMEDA trial evaluating daratumumab, bortezomib, cyclophosphamide, and dexamethasone (D-VCd) versus VCd alone with newly diagnosed AL amyloidosis found that patients with clinical improvement following systemic therapy for AL amyloidosis experience small but meaningful improvements in HRQOL and symptoms 14. During treatment, score changes from baseline in PRO measures including the SF-36, EQ-5D, and EORTC QLQ-C30, albeit small in magnitude, generally favored D-VCd over VCd alone 14.…”
mentioning
confidence: 99%